Total Vitamin C, Ascorbic Acid, Dehydroascorbic Acid, Antioxidant Properties, and Iron Content of Underutilized and Commonly Consumed Fruits in Sri Lanka - Hashini I. Abeysuriya; Vajira P. Bulugahapitiya; Jayatissa Loku Pulukkuttige (International Journal of Food Science)
Sri Lanka is rich in a wide diversity of fruits, but many are underutilized by the people in Sri Lanka despite their nutritional value. This is mainly due to little awareness of the palatability of many fruits and hence low popularity in the market. The present study aimed at providing comparative data on the main biochemical and nutritional parameters of thirty-seven (37) species of fruits grown in Sri Lanka, including 22 underutilized fruits and 15 commonly consumed fruits. The main parameters of the comparison were the contents of ascorbic acid (AA), total vitamin C (TVC), total phenolic content (TPC), total flavonoid content (TFC), total iron (Fe), and antioxidant capacities (ACs). The mean AA, TVC, TPC, TFC, and Fe contents in 100 g of fresh edible portions of fruits ranged from 2.0 to 185.0 mg, 8.1 to 529.6 mg, 12.9 to 2701.7 mg gallic acid equivalent, 0.2 to 117.5 mg quercetin equivalents, and 0.1 to 1.1 mg, respectively. The IC50 values in a DPPH assay varied between 0.8 to 1856.7 mg/mL and FRAP values in a FRAP assay ranged from 4.2 to 2070 μmol FeSO4/g in the studied fruits. Fruits were ranked based on the levels of the abovementioned biochemical properties. Using this ranking, 12 of the top 15 fruits were underutilized. Phyllanthus emblica (Indian gooseberry) is at the top of these underutilized fruits, and Psidium guajava (guava) is the best among commonly consumed fruits. These results indicate that underutilized fruits in Sri Lanka can be recommended as high quality and low-cost alternatives for securing nutritional requirements. Hence, underutilized fruits can be promoted as healthy additional fruits in Sri Lanka.